Technical Systems Under Stress: New Lifespan Models and Calculation Methods - Mine Doğan; Mehmet Gürcan (AppliedMath)
Technical systems, which form the basis of modern technology, are structures designed to achieve a specific purpose by bringing together different components. In this respect, they have a wide field of study. Our study is aimed at the general evaluation of technical systems operating under stress. The reliability of technical systems is directly related to order statistics. Therefore, first of all, when the moment of failure is observed, a life time distribution is proposed, which is revised at each moment of failure. Secondly, a new expected value operator is proposed. Thanks to this operator, the average working time under stress can be calculated easily without deforming the working time distribution. Finally, the differential structure of the stress factor is examined in detail, and two different differential equations and solutions are proposed depending on the working time distribution. The numerical calculations presented in the study include detailed information on the applications of the proposed methods.